Meningitis as a rare cause of delirium in burn patient: Case report - Sarah Sabur; Amine El harti; Chaymaa Benyamna; Sara Karti; Ahlam El Youssoufi; Marouane Habla; Mounia Diouri (Burns Open)
Delirium is an acutely disturbed state of mind or consciousness frequent in patients with extensive burns. The causes are multiple but CNS (central nervous system) infection is among the rare and severe causes of delirium with high fever in burn patients and with the lack of fast and correct diagnosis and adequate treatment, the prognosis is mostly severe. Even with the presence of other causes of delirium in burn patients, the CNS infection must be excluded first, especially when we have a massive bacteremia.